Measurement of Cost of Capital for Foreign Direct Investment in Pakistan: A Neoclassical Approach (The Pakistan Development Review, 2002)
Capital can move inside and outside the boundaries of a country in search of the highest financial return and greatest security for its operation in the host regions. High return from investment is linked with the incentive mechanism offered by the host country in attracting FDI to fill the investment gap and diffusion of other skills. To attract the foreign investors, the successive governments in Pakistan, offered various investment incentives in the form of tax concessions (tax expenditure) and direct expenditure on infrastructural provisions. The taxation policy of Pakistan has great relevance for Transnational Corporation’s (TNC) involvement in production activities. It is perceived to be a significantly influential factor in determining the inflow of foreign investment through the cost of capital and the resulting after tax return. Stimulating foreign investment, mainly through the large TNCs, requires cost minimising devices, which are reflected in fixed cost of a long-term investment project. The cost of fixed assets in such projects depends upon the rate of return, the price of capital goods and, most importantly, the tax treatment of generated income. Foreign investors are generally pursuing two sets of objectives that are related to their decision to invest. First, they prefer for locational advantages like market size, access to raw material and the availability of skilled labour. Secondly, they have their concern with the incentives offered by the host countries through their fiscal policies. These policies attract the investment considerations of the foreign investors. TNCs search the second set of objectives only if the first set is fulfilled.